Variability in marsh migration potential determined by topographic rather than anthropogenic constraints in the Chesapeake Bay region. Issue 4 (31st May 2022) - Molino, Grace D.; Carr, Joel A.; Ganju, Neil K.; Kirwan, Matthew L.
Abstract: Sea level rise (SLR) and saltwater intrusion are driving inland shifts in coastal ecosystems. Here, we make high‐resolution (1 m) predictions of land conversion under future SLR scenarios in 81 watersheds surrounding Chesapeake Bay, United States, a hotspot for accelerated SLR and saltwater intrusion. We find that 1050–3748 km 2 of marsh could be created by 2100, largely at the expense of forested wetlands. Predicted marsh migration exceeds total current tidal marsh area and is ~ 4× greater than historical observations. Anthropogenic land use in marsh migration areas is concentrated within a few watersheds and minimally impacts calculated metrics of marsh resilience. Despite regional marsh area maintenance, local ecosystem service replacement within vulnerable watersheds remains uncertain. However, our work suggests that topography rather than land use drives spatial variability in wetland vulnerability regionally, and that rural land conversion is needed to compensate for extensive areal losses on heavily developed coasts globally.